Online non-contact quality control of noodle dough using ultrasound. (October 2019) - Kerhervé, S.O.; Guillermic, R.-M.; Strybulevych, A.; Hatcher, D.W.; Scanlon, M.G.; Page, J.H.
Abstract: The development of a non-contract ultrasonic technique is reported for online quality control of noodle dough without compromising food safety during production. The technique uses airborne ultrasound to measure mechanical properties of the dough without touching or deforming it; thus, food safety cannot be endangered during processing by contamination arising from direct contact with monitoring equipment. Measured mechanical properties are related to the texture of the final product, thereby providing information during processing that is relevant to product quality. The technique was first assessed in laboratory experiments and then tested online during production runs on a pilot plant noodle sheeting line. It was found that differences in mechanical properties of noodle doughs resulting from changes in formulation or processing conditions can be distinguished, and that flaws arising from thickness fluctuations in noodle sheets can be detected. These offline and online experiments show the feasibility of using non-contact ultrasound for real-time hygienic quality monitoring of noodles at critical control points in the sheeting process, thereby providing rapid feedback for improvements in process design and control. Highlights: Non-contact ultrasound is sensitive to formulation and processing of Asian noodles. Online ultrasonic monitoring of noodle dough's mechanical properties is feasible. Process control of noodle dough during sheeting is enabled by an ultrasonic method. Ultrasonic technique can detect thickness flaws in noodle dough during production.